Efeito da herança: trajetórias familiares e o investimento em colégios militares - Rosa, Gabriel Claro da (2023)
The concern with the quality of education offered in schools is an issue that permeates the most diverse families, those who are presented with the possibility of choosing one or another educational institution, end up seeing in the results of the Enem (National High School Examination) and Entrance exams are an item to be strongly considered when making a decision; thus, Military Colleges attract attention. However, linking the choice of countless families for Military Colleges solely to the results of their students in the Enem is to reduce the discussion about the schooling process and, subsequently, the entry of young people into Higher Education. The study is based on the theoretical assumptions of sociologist Pierre Bourdieu, which allowed us to see a generational investment in the schooling process, showing here on the part of families a strategic calculation that makes them see in the Military College an objective possibility of social change based on acquisition of school capital. Through questionnaires and interviews carried out with fathers, mothers or family members responsible for young people studying in Military Schools, we sought to understand the trajectory and perception about public education on the part of families in Rio Grande do Sul who opted for military schools to educate their children and daughters and the motivators for such a choice. The study demonstrated similarities in origin, academic and professional trajectory of the study participants, as well as showing that the choice of a military education institution is based, among other factors, on the disqualification of regular public education and the social class of the participants in the search.